2000
DOI: 10.1128/jvi.74.6.2502-2509.2000
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Modified Vaccinia Virus Expressing Simian Immunodeficiency Virus (SIV) Gag-Pol Primes for an Anamnestic Gag-Specific Cytotoxic T-Lymphocyte Response and Is Associated with Reduction of Viremia after SIV Challenge

Abstract: The immunogenicity and protective efficacy of a modified vaccinia virus Ankara (MVA) recombinant expressing the simian immunodeficiency virus (SIV) Gag-Pol proteins (MVA-gag-pol) was explored in rhesus monkeys expressing the major histocompatibility complex (MHC) class I allele, MamuA*01. Macaques received four sequential intramuscular immunizations with the MVA-gag-pol recombinant virus or nonrecombinant MVA as a control. Gag-specific cytotoxic T-lymphocyte (CTL) responses were detected in all MVA-gagpol-immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 53 publications
8
76
2
Order By: Relevance
“…Vaccine strategies which elicit potent cytotoxic T cell (CTL) responses lead to reduced virus loads and long-term protection against immunodeficiency disease in macaque challenge studies using simian immunodeficiency virus (SIV) or pathogenic simian-human immunodeficiency virus chimeras (SHIV) [8,9]. It has been recently reported that viral escape from CTL recognition can result in the eventual failure of the immune protection induced by candidate AISD vaccines [10] and rhesus macaques infected with SIV/SHIV show significantly higher viral loads if CD8+ T cells are eliminated [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine strategies which elicit potent cytotoxic T cell (CTL) responses lead to reduced virus loads and long-term protection against immunodeficiency disease in macaque challenge studies using simian immunodeficiency virus (SIV) or pathogenic simian-human immunodeficiency virus chimeras (SHIV) [8,9]. It has been recently reported that viral escape from CTL recognition can result in the eventual failure of the immune protection induced by candidate AISD vaccines [10] and rhesus macaques infected with SIV/SHIV show significantly higher viral loads if CD8+ T cells are eliminated [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…T-cells are also important for control of SIV in the macaque model of AIDS. CD8+ T-cells elicited by vaccines are responsible for reducing viral load [2,[8][9][10][11]. Conversely, in vivo depletion of CD8+ T-cells prior to challenge with SIV results in uncontrolled viral replication [12].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst immunization with simian immunodeficiency virus (SIV) Gag, alone or in combination with HIV-1 Env or Nef and Tat, has already yielded promising results, the data must be interpreted with caution as, in most cases, Mamu A*01-positive animals, which mount a particularly robust response to highly conserved Gag peptides, were used (Amara et al, 2001(Amara et al, , 2002Barouch et al, 2001;Casimiro et al, 2005;Egan et al, 2004;Montefiori et al, 1996;Mooij et al, 2004;Seth et al, 2000;Shiver et al, 2002). Importantly, previous work using an adjuvanted protein vaccine based on Env, Nef and Tat antigens suggested protection from SHIV-induced sustained virus load and CD4 T-cell decline in rhesus monkeys (Voss et al, 2003).…”
Section: Introductionmentioning
confidence: 99%